2008
DOI: 10.1007/s10531-008-9500-7
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal, habitat and substrate distribution patterns of freshwater ascomycetes in the Florida Peninsula

Abstract: Freshwater ascomycetes are important decomposers of dead woody and herbaceous debris in aquatic habitats. Despite evidence of their ecological importance, latitudinal, habitat and substrate distributional patterns of freshwater ascomycetes are poorly understood. In this study, we examined the latitudinal and habitat distributional patterns, and substrate recurrences of freshwater ascomycetes by collecting dead submerged woody and herbaceous debris in lentic and lotic habitats at five selected sites along a nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 86 publications
1
42
1
Order By: Relevance
“…Methods for collection, isolation, morphological characterization, and illustration of freshwater ascomycetes used in this study are described by Shearer et al (2004) and Raja et al (2009). The holotype and additional specimens are deposited in the Herbarium of the University of Illinois at Urbana-Champaign (ILL).…”
Section: Morphological Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Methods for collection, isolation, morphological characterization, and illustration of freshwater ascomycetes used in this study are described by Shearer et al (2004) and Raja et al (2009). The holotype and additional specimens are deposited in the Herbarium of the University of Illinois at Urbana-Champaign (ILL).…”
Section: Morphological Studymentioning
confidence: 99%
“…During studies of freshwater ascomycetes along a latitudinal gradient through North and Central America, an unusual bitunicate fungus was found on submerged wood and herbaceous material in Florida (as F76 in Raja et al 2009) and on submerged wood in Costa Rica. Morphological characters such as presence of a globose, immersed to erumpent pseudothecium with a pseudoparenchymatous peridium, interascal tissue of cellular pseudoparaphyses, fissitunicate asci, and thin-walled, hyaline, one-septate ascospores with a gelatinous sheath are characteristics of taxa in the order Pleosporales (Dothideomycetes).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, very few studies have focused on aquatic fungal diversity patterns at large spatial scales (Ho et al 2001;Arnolds 2007;Raja et al 2009). Based on a compilation of data extracted from the literature, Shearer et al (2007) concluded that the species richness of aquatic hyphomycetes in streams appeared to exhibit maxima in temperate rather than tropical climates, and suggested that this pattern might be driven by more varied ecological niches in temperate climates, resulting from stronger seasonality than in the tropics.…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports on freshwater fungi from both lentic and lotic habitats in different areas (Raja et al 2009;Cai et al 2002Cai et al , 2006Nikolcheva et al 2005;Pascoal and Cássio 2004;Rajashekhar and Kaveriappa 2003;Tsui et al 2001aTsui et al , b, 2003Sivichai et al 2002Sivichai et al , 2000Ho et al 2001;El-Hissy et al 2000;Hyde and Goh 1999;Raviraja et al 1998) and much has been written on the subject .…”
Section: Introductionmentioning
confidence: 99%